User Behavior and Technology Development Shaping Sustainable Relations Between Consumers and Technologies - Verbeek, Peter-Paul; Slob, Adriaan (Eco-Efficiency in Industry and Science, 2006)
Environmental policy has long been determined by a dichotomy between technology and behavior. Some approaches stress the importance of technology and technological innovation, while others focus on behavioral change. Each approach has its limitations, however, since technology and behavior often appear so closely intertwined. Human behavior results not only from intentions and deliberate decisions, but also from its interaction with technological artifacts. In the area of traffic safety, for instance, people's driving behavior is determined as much by curves, speed bumps and the power of their motors as by considerations of safety and responsibility. How can we best describe and understand these interactions between behavior and technology? What conceptual frameworks and empirical studies are available, and how can they be integrated? And how can we bring these interactions to bear on product design and policy making? The book User Behavior and Technology Development explores these relationships between technology and behavior from an interdisciplinary perspective. This includes contributions from cognitive psychology, industrial design, public administration, marketing, sociology, ergonomics, science and technology studies, and philosophy. The book aims to create a conceptual basis for analyzing interactions between technology and behavior, and to provide insights that are relevant to technology design and environmental policy.